2017
DOI: 10.3390/w9080567
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SWAT and GWLF Model Simulation Performance in Humid South and Semi-Arid North of China

Abstract: Watershed models have gradually been adapted to support both decision and policy making for global environmental pollution control. In this study, two watershed models with different complexity, the Soil and Water Assessment Tool (SWAT) and the Generalized Watershed Loading Function (GWLF), were applied in two catchments in data scarce China, namely the Tunxi and the Hanjiaying basins with contrasting climatic conditions (humid and semi-arid, respectively). The performances of both models were assessed via com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Based on the outputs of the model applications, the non-point sources from farmland discharge through runoff and septic systems discharge through groundwater were detected as the current main contributing sources of Dis-P in studied watershed. The fluxes and source apportionments of Dis-P were variable in different months, in accordance with previous studies [34,46,47,49].…”
Section: Property Of Phosphorus Apportionment and Potential Contributsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the outputs of the model applications, the non-point sources from farmland discharge through runoff and septic systems discharge through groundwater were detected as the current main contributing sources of Dis-P in studied watershed. The fluxes and source apportionments of Dis-P were variable in different months, in accordance with previous studies [34,46,47,49].…”
Section: Property Of Phosphorus Apportionment and Potential Contributsupporting
confidence: 90%
“…However, both the R 2 NS and r 2 were higher than 0.80 in the calibration period and that both statistics declined slightly in the verification period but neither was below 0.75. Such statistics were in accordance with the standard level of watershed model applications for the estimation of the monthly hydrological process [45,46], and all the calibrated transport parameter values could make sense within reasonable physical range, which indicated that the calibrated ReNuMa model could provide reliable modeling of the watershed hydrological processes, based on which the nutrient parameters of ReNuMa could be estimated for Dis-P modeling.…”
Section: Renuma Modelsupporting
confidence: 74%
“…19-Qi et al [41] compared SWAT to a simpler Generalized Watershed Loading Function (GWLF) model. The performances of both models were assessed via comparison between simulated and measured monthly streamflow, sediment yield, and total nitrogen.…”
Section: Appendix Amentioning
confidence: 99%
“…It was also tested and used in many regions in Africa [26][27][28][29][30][31][32][33] to estimate sediment yields from both gauged and ungauged watersheds and good results were reported. Similarly, the performance of SWAT model was tested in Germany [34], USA [35], China [36][37][38][39][40] and Jamaica [41] to predict the amount of sediment as well as stream flow from gauged and ungauged river basins Due to its wide applicability, SWAT model was selected in this study to estimate the sediment yield of Lake Ziway basin, Ethiopia. The SWAT model is a watershed scale model that incorporates the features of several other models [42].…”
Section: Introductionmentioning
confidence: 99%